Safety, Tolerability, and Pharmacokinetics of Adrenomedullin in Healthy Males: A Randomized, Double-Blind, Phase 1 Clinical Trial - Kita T; Kaji Y; Kitamura K (Dove Medical Press, 2020)
Toshihiro Kita,1 Yoshikazu Kaji,2 Kazuo Kitamura1 1Division of Circulatory and Body Fluid Regulation, Department of Internal Medicine, Faculty of Medicine, University of Miyazaki, Miyazaki, Japan; 2Souseikai Hakata Clinic, Fukuoka, JapanCorrespondence: Toshihiro KitaDivision of Circulatory and Body Fluid Regulation, Department of Internal Medicine, Faculty of Medicine, University of Miyazaki, 5200 Kihara, Miyazaki 889-1692, JapanTel +81-985-85-0872Fax +81-985-85-6596Email toshihiro_kita@med.miyazaki-u.ac.jpBackground: Adrenomedullin (AM), an endogenous vasodilative peptide, has immunomodulative effects and acts as an accelerator of mucosal regeneration in the digestive tract. AM has shown beneficial effects in rodent models of inflammatory bowel disease and patients with ulcerative colitis. The present study aimed to evaluate the pharmacodynamic properties and safety of AM in healthy male adults in a phase 1 clinical trial.Methods: This phase 1, randomized, double-blind, single-center study was conducted on healthy males aged 20–65 years. Subjects received either a placebo, 3 ng/kg/min AM, 9 ng/kg/min AM, or 15 ng/kg/min AM via continuous 12-h intravenous infusion. Other subjects received either placebo or 15 ng/kg/min AM for 8 h per day for 7 days. Adverse events (AEs), vital signs, physical examinations, laboratory tests, electrocardiograms (ECG), and pharmacokinetics were assessed.Findings: All 24 subjects in the single-dose test completed the study. Of the 12 subjects in multiple dosing test, one from the AM group withdrew owing to a headache. No serious AEs were reported. Hemodynamic parameters were well maintained in all subjects. Slight ECG abnormalities were observed in the single-dose test. The plasma concentration of AM progressively increased in a dose-dependent manner and reached Cmax at the end of administration. Plasma AM rapidly returned to baseline concentrations after termination, with a T1/2 of under 60 min.Interpretation: This is the first phase 1 trial in healthy men evaluating the safety of AM. Our results demonstrate the safety and tolerability of AM for subsequent Phase 2 trials.Keywords: adrenomedullin, Phase 1 clinical trial, clinical pharmacology, inflammatory bowel disease